FAKTOR YANG MEMENGARUHI RISIKO SISTEMATIS PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nurshadrina Kartika Sari (RELASI : JURNAL EKONOMI, 2012)
This Research was conducted at the banks listed on the Indonesia Stock Exchange 2007 to 2009 period, with samples obtained using purposive sampling as many as eleven (11) banks. Beta is measure of systematic risk of shares of a security or portfolio relative to the market risk. The results of the analysis performed using multiple linear regression to determine which of the Asset Growth, Debt to Equity Ratio, Return on Equity and Earning Per Share affecting the Beta Shares, the results showed that four variables had no effect on beta bank stocks listed in Indonesia Stock Exchange 2007-2009.